The performance of uncoated tungsten carbide insert in end milling titanium alloy Ti-6Al 4V through work piece preheating - Ginta, Turnad Lenggo; Lajis, Mohd Amri; Amin, A. K. M. Nurul (Science Publications, 2009)
Problem statement: Titanium alloys have been used widely in the aerospace, chemical and petroleum industry because of their high specific strength, fracture resistance and superior resistance to corrosion. Titanium alloys have a very high strength-to-weight ratio making them very suitable for aircraft engines and airframe manufacture.